NLRP3-Mediated Inflammation in Atherosclerosis and Associated Therapeutics - Lu, Na; Cheng, Weijia; Liu, Dongling; Liu, Gang; Cui, Can; Feng, Chaoli; Wang, Xianwei (Frontiers in Cell and Developmental Biology, 2022)
The NLRP3 inflammasome is an important part of the body's innate immune system, and a multiprotein platform which is activated by recognizing pathogen-associated molecular patterns (PAMPs) or damage-associated molecular patterns (DAMPs) through the form of PRRs. Its activation leads to caspase-1-dependent secretion of proinflammatory cytokines like interleukin-1β (IL-1β) and IL-18, and an inflammatory form of cell death termed as pyroptosi s. Recent studies have confirmed that NLRP3 inflammasome overactivation causes severe inflammatory responses and is involved in the development of atherosclerosis. Therefore, the development of specific inhibitors in the NLRP3 inflammasome and the upstream and downstream inflammatory factors has become potential targets for clinical treatment. Here we review recently described mechanisms of the NLRP3 inflammasome activation, and discuss emphatically the therapeutic effect of statins and natural medication on atherosclerosis associated with NLRP3 inflammasome.